Leveraging the participation of small and medium-sized enterprises in global value chains of the automotive industry: Insights from Maruti Suzuki India Limited - Falendra Kumar Sudan (Asian Development Bank Institute (ADBI), 2020)
The existing potential of SMEs remains untapped in most developing countries, including India. In India, most SMEs have a lower share of foreign goods and services to produce exports than larger firms. Moreover, dependent SMEs also have greater integration in terms of imports than independent SMEs and are better equipped to overcome import trade barriers. Therefore, robust policies are essential to address the export and import constraints faced by SMEs. SMEs also face certain risks in global value chain (GVC) participation due to weaker bargaining power vis-à-vis larger firms, which calls for the creation of a level playing field. Against the above backdrop, the present study intends to analyze the role of SMEs engaged in the automotive sector in GVCs using a qualitative case study of Maruti Suzuki India Limited (MSIL) as a lead firm and how this role could be enhanced by government support. The study reveals that GVC participation benefits SMEs modestly; however, restructuring production through subcontracting can facilitate economic, industrial, functional, human, and technical upgrading. Government should extend necessary support to SMEs for the development of new alliances and comprehensive networks of upstream and downstream partners through information flow, access to the latest technology, learning opportunities, and acquisition of knowledge for high value added.
Keywords: L62; F15; L29; 330; automotive industry; global value chains; small and medium enterprises; India